(untitled) (Anclajes, 2021)
Studies on nineteenth-century literature are relatively scarce in academic criticism. This corpus might be examined from a perspective of "eye of the Pampa"; that is, a reading that allows us to understand axes of the Argentine intellectual debate that intersect cultural and political memory. In this sense, I review some articles published in Anclajes that contribute to under-examined topics, such as the recovery and study of literature written by women and other areas not explored by the metropolitan imaginary.